AS CONTRIBUIÇÕES DA LUDICIDADE NA DINAMIZAÇÃO DA PROPOSTA CURRICULAR DE UMA ESCOLA DO CAMPO LOCALIZADA NO MUNICÍPIO MARAJOARA DE BREVES-PA - SANTOS, Raila Trindade dos (2024)
This course conclusion work aimed to analyze the contribution of playfulness in the dynamization of the curricular proposal of a field school, located in the city of Breves- Pará. This research proposed to answer the following main question: How can playfulness contribute to the dynamism of the curricular proposal of a field school located in the marajoara municipality of Breves-PA? The guiding questions tied to this research problem were: What is the space occupied by recreational activities in the curricular guidelines for field education in Brazil, as well as in the curricular proposal of the field schools of the Municipality of Breves-Pará? How do playful activities contribute to the learning of content related to the generating themes of the curricular proposal of the field schools located in the municipality of Breves-Pará? What are the contributions of the extension project “Playful Activities for the Curriculum of Field School in the Marajoara Municipality of Breves-Pará” for the insertion or increase of playful activities in this curricular proposal? For its execution, a bibliographic search was carried out. Subsequently, a qualitative approach was chosen, having as procedures the field research and the case study that occurred from the extension project. For an analysis of the data obtained, we used a content analysis. The discussions of this research have as its theorical base Caetano (2013), Almeida (2015), Ritter (2016), Evaristo (2017) and Rolim (2017), we also analyzed official documents such as the Operational Guidelines for Basic Education in Field Schools (BRAZIL, 2002) and the Curriculum Proposal (final years) for Elementary Field Schools (BREVES, 2014). The research results show that playfulness contributes to the teaching and learning process, as it provides a pedagogical practice that stimulates students in a more dynamic way. It was also observed that the extension project had great relevance for the São Pedro school, as it provided training for teachers, who despite demonstrating knowledge about playfulness and using it in the classroom, they used it out of context. The actions that the project developed, they contributed so that teachers could perform a pedagogical work linked to playfulness in a systematic way, sharing and building knowledge, through a moment of exchange of experience.